Self-digital como uma perspectiva sobre a construção das identidades organizacionais nas mídias sociais - Oliveira, Tatiane Rodrigues C. de (2019)
The study consists of reflection about the transformations in the processes of the identity formation of organizations with the social media. Taking as theoretical-methodological reference the paradigm of the complexity of Edgar Morin, in addition to the studies proposed by George Herbert Mead, Erving Goffman and Anthony Giddens on identity, presents a new concept, the self-digital. The self-digital is the reflexivity of the self in the digital environment. It is a kind of character in social media, reaffirmed by the construction of narratives through texts and images, which enable their recognition and social legitimation. In this context, organizations make up their self-digital in a complex, provisional, symbolic and interactive way. Organizational communication is woven as a guideline for the construction of these narratives and the images gain relevance because they allow symbolic interaction, a link of approximation, and fill the physical absence of social media. It is the images that represent the world, the companies, define behaviors, take experiences, styles and thus create models that lead us to the sensation of hyper-reality, of mythological/magical thinking. In this work, we propose a method for image analysis in social media and applied it to evaluate two public banks in Instagram, Caixa Econômica Federal and Banco do Brasil. It is observed that the interaction with the images of these companies, over time, generates an identification and relational process, of symbolic connection with the users in the digital environment, that has frailties and can be affected at any moment.